Gender Narratives in Popular Media: A Humanities Study of Women’s Representation and Resistance - Firayani (Kamara Journal, 2026)
Popular media functions as a powerful symbolic arena where gender meanings are produced, circulated, and contested. Women’s bodies and identities are frequently framed through stereotypical, subordinated, and commodified representations that reinforce patriarchal, class-based, racial, and religious hierarchies. At the same time, contemporary media landscapes provide spaces for negotiation and resistance, allowing women to challenge dominant narratives through digital activism, counter-representation, and postfeminist storytelling strategies. This study aims to critically analyze how gender narratives in popular media simultaneously construct and contest structures of power over women and to demonstrate how humanities approaches can illuminate this dynamic tension. The research employs a qualitative design integrating critical discourse analysis, visual semiotics, and intersectional feminist theory to examine selected films, digital media content, and popular narratives. The findings reveal that representation and resistance coexist dialectically: while media texts continue to reproduce hegemonic gender norms, they also embed counter-hegemonic discourses that reposition women as narrative subjects rather than passive objects. Intersectional factors such as class, caste, race, religion, and profession significantly mediate both vulnerability and resistance. The study concludes that popular media is not merely a mirror of inequality but a contested cultural field where symbolic domination and female agency continuously interact